Prolonged Inheritance Distribution: The Perspective Of Al Maslahah And Legal Certainty - Kuswoyo, Bahet Edi; Reyzaldi Fitrananda; Moh. Adrian; Renny Fusvitasari; M. Wildan Murtadho Al Idrus; Mukhtar; S, Kholil (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2026)
Prolonged inheritance distribution is a recurring phenomenon in Muslim society that often gives rise to legal uncertainty, family conflict, and the neglect of the objectives of Islamic law. This study examines the issue of delayed inheritance distribution from the perspective of al-maslahah and legal certainty, highlighting the tension between normative Islamic inheritance rules and their practical application. The research employs a normative legal method combined with an empirical (socio-legal) approach. Normative analysis is conducted by examining statutory regulations, court decisions, and doctrines of fiqh and ushul fiqh related to inheritance law, with particular attention to the principles of al-maslahah and legal certainty. The empirical approach is employed to investigate the social realities that contribute to the delay in inheritance distribution, including family dynamics, cultural considerations, psychological factors, and institutional practices. This approach is essential because prolonged inheritance cases are not merely normative legal issues but are also influenced by non-legal factors embedded in social life. By integrating normative and empirical perspectives, this study provides a comprehensive understanding of the causes and implications of delayed inheritance distribution. The findings are expected to contribute to the development of a more responsive and just framework for inheritance law that upholds al-maslahah and ensures legal certainty in Islamic inheritance practices.